FAKTOR PRNENTU KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA TENGAH (Studi Kasus Pada Kabupaten/Kota Se-Jawa Tengah Tahun 2015-2017) - Ernawati Ernawati; Jaeni Jaeni (Faculty of Economic and Business Universitas STIKUBANK, 2018)
This study aims to analyze the Determinants of Financial Performance of District / City Governments in Central Java Province. This study discusses the financial determinants of local government using proxy measures (size), Prosperity (wealth), legislative measure, intergovernmental income and leverage.This study discusses the Local Government Financial Report (LKPD) by taking a sample of 35 districts / cities in Central Java in 2015-2017. The data used in this research is secondary data. The analytical tool used in this research is multiple linear regression. The results of this study show that the size of the Regional Government and Prosperity is not related to the financial performance of the Regency / City of Central Java Province in 2015-2017. While Legislative Measures play a significant negative role in the Financial Performance of District / City Governments in Central Java in 2015-2017, and Intergovernmental Income and Leverage does not affect the financial performance of Regency / City Governments in Central Java in 20015-2017. Keywords: financial performance, local government size, prosperity, legislative size, intergovernmental income, and leverage.